Barriers to cervical screening among older women from hard-to-reach groups: a qualitative study in England - Laura Marlow; Emily McBride; Laura Varnes; Jo Waller (BMC, 2019)
Abstract Background Cervical screening attendance among 50-64 year-olds is suboptimal. Understanding attitudes to screening and reasons for non-attendance in older women will help to identify the content of interventions for this age group. This study aimed to explore barriers to cervical screening among women aged 50-64 years from hard-to-reach groups whose perspectives are often absent from research on cervical screening but are critical to developing appropriate interventions to increase engagement with the screening offer. Methods Qualitative methodology was used. Six focus groups were carried out with women aged 50-64 years from lower socio-economic and ethnic minority backgrounds (n = 38). Focus group discussions were recorded, transcribed verbatim and translated where necessary. Data were analysed using the Framework Approach, a type of thematic analysis. Results All women had heard of cervical screening, but many felt they had poor knowledge. Women's reasons for non-attendance were wide-ranging and included discomfort and embarrassment, negative perceptions of health professionals, worry and trust in the results, concern about the procedure, idiosyncratic beliefs, and extreme negative experiences. Some women reported not receiving letters or prompts to be screened. Conclusions Information designed specifically for older women should ensure they understand the purpose of screening and its relevance to them. Emphasising changes to the programme that have made the experience less uncomfortable, and improved sample taker awareness of how women feel, may help to allay concerns related to previous negative experiences.